1996
DOI: 10.1002/(sici)1097-4644(19960301)60:3<341::aid-jcb6>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional downregulation of stromelysin by tetracycline

Abstract: We investigated the role of tetracycline in the transcriptional regulation of matrix metalloproteinases. Using interleukin-1beta (IL-1) induced stromelysin as a model system, we describe the repression of the endogenous stromelysin RNA accumulation, as well as the transcriptional inhibition of various stromelysin promoter/chloramphenicol-acetyltransferase constructs in transient transfection assays. The inhibition occurred in a dose-dependent fashion, with an IC50 of about 1 microM. Our results suggest that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
26
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 35 publications
2
26
0
Order By: Relevance
“…Inhibition of MMPs could also be related to inhibition of the transcription of MMP mRNAs. 30 In our study, doxycycline significantly reduced aortic MMP-2 upregulation and MMP-2 activity in the 2 types of arteries. This suggests that it could act on MMP-2 expression, activation, The values of M/L ratio and CSA at 28 days are also presented in Figure 1; *PϽ0.05 vs control; †PϽ0.05 vs L-NAME alone.…”
Section: Discussionsupporting
confidence: 60%
“…Inhibition of MMPs could also be related to inhibition of the transcription of MMP mRNAs. 30 In our study, doxycycline significantly reduced aortic MMP-2 upregulation and MMP-2 activity in the 2 types of arteries. This suggests that it could act on MMP-2 expression, activation, The values of M/L ratio and CSA at 28 days are also presented in Figure 1; *PϽ0.05 vs control; †PϽ0.05 vs L-NAME alone.…”
Section: Discussionsupporting
confidence: 60%
“…The observation that oral administration of doxycycline markedly reduces the level of total collagenase protein, and not only collagenase activity, in extracts of canine (34,35) and human (36) OA cartilage suggests that, in addition to inhibiting the activity of some MMPs, the drug affects the production and accumulation of MMPs. The effect may be exerted through reduction of enzyme stability, as indicated by studies with recombinant MMP-8 (15) and MMP-13 (37), through inhibition of transcription, as has been shown for MMP-3 in fibroblasts (38) and for MMP-13 in human OA chondrocytes (39), or through inhibition of translation, as has been shown for type X collagen in senescent chick chondrocytes (40).…”
Section: Discussionmentioning
confidence: 99%
“…• Indirect effects on endogenous activators and inhibitors that regulate MMP's activity [8,[39][40][41].…”
mentioning
confidence: 99%
“…Hence, in present study docking analysis of violacein with MMP2 and MMP9 was performed to get the possibility of direct active site inhibition to treat cerebral ischemia. A study by Kiyama et al suggested that MMP9 consists of S1'cavity pocket with a floor board and MMP2 have S1'channel like cavity [41]. The S1' pocket of MMP9 consists of Asp185 to Leu188 and Pro421 to Tyr423 residues which are effective for inhibition and substrate binding [43].…”
mentioning
confidence: 99%